الاغتراب النفسي وعلاقته بالصحة النفسية لدى طلاب ا لجامعة - عبدالله, عبدالله (University of Eloued جامعة الوادي, 2020)
دفت الدراسة إلى الكشف عن طبيعة العلاقة بين الشعور بالاغتراب النفسي والشعور بالصحة النفسية لدى طلبة الجامعة، ومعرفة الفروق تبعاً : للجنس ونوع الكلية والتخصص الأكاديمي والمستوى الجامعي ومكان السكن. والتعرف على مستوى درجة الصحة النفسية لدى الطلاب ومعرفة الفروق تبعاً للجنس ونوع الكلية والتخصص الأكاديمي والمستوى الجامعي ومكان السكن. ولقد تم تطبيق مقياس الاغتراب للمرحلة الجامعية ، ومقياس الصحة النفسية على عينة عشوائية مكونة من 260 طالب وطالبة . وبعد التحليل الإحصائي أظهرت النتائج وجود علاقة ارتباطيه سلبية عكسية متوسطة بين ظاهرة الاغتراب والشعور بالصحة النفسية لدى طلاب الجامعة. كما وجد هناك فروقاً دالة في ظاهرة الاغتراب لدى الطلاب تبعاً للجنس لصالح الإناث. ووجود فروق تبعاً للكليات الأدبية والكليات العلمية لصالح الكليات الأدبية. ووجود فروق دالة في ظاهرة الاغتراب تبعاً لنوع السكن لصالح الطلاب الذين يسكنون في الإقامة الجامعية. ووجود فروق دالة في ظاهرة الاغتراب لدى طلاب الجامعة تبعًا للتخصص الأكاديمي وللمستوى الجامعي. كما وجد هناك فروق ذات دلالة إحصائية في درجة الصحة النفسية لدى الطلاب تبعًا للكليات الأدبية والعلمية باتجاه درجات الكليات الأدبية. كما وجد فروق ذات دلالة إحصائية في درجة الصحة النفسية لدى الطلاب تبعًا للتخصص الأكاديمي وتبعاً للمستوى الجامعي في حين لا توجد فروق في درجة الصحة النفسية لدى الطلاب تبعًا للجنس ونوع السكن للطلاب. الكلمات المفتاحية : الاغتراب النفسي- الصحة النفسية The study aimed to reveal the nature of the relationship between the psychological feeling of alienation and a sense of mental health among university students, and to know the differences depending on : sex and type of each yeh and the academic specialization wa to university level and place of residence. And to identify the degree of mental health level of students and knowledge of the differences depending on sex and type of each yeh and the academic specialization wa to university level and place of residence. The university's alienation scale and the mental health scale were applied to a random sample of 260 students . After the statistical analysis , the results showed an adverse negative correlation between the phenomenon of alienation and a sense of mental health among university students . Also it found there are differences function in the phenomenon of alienation among students by sex in favor of females . And the existence of differences according to the literary colleges and scientific colleges in favor of the literary colleges. And the presence of significant differences in the phenomenon of alienation according to the type of housing for the benefit of students who live in university residence. And the presence of significant differences in the phenomenon of alienation among university students, according to academic specialization and university level . There were also statistically significant differences in the degree of mental health among students according to literary and scientific colleges towards the degrees of literary colleges . Differences also found statistically significant differences in the degree of mental health of the students followed a For academic specialization and according to the university level, while there are no differences in the degree of mental health of students according to gender and type of housing for students
Psychological alienation and its relationship to mental health among university students A field study on a sample of university students in Algiers - June 2009
مجلة الدراسات والبحوث الاجتماعية المجلد 08 العدد 01 جامعة
Keywords: الاغتراب النفسي- الصحة النفسية; psychological alienation - mental health